Formulation for multiple curved crack problem in a finite plate - Ghorbanpoor, R.; Nik Long, Nik Mohd Asri; Eshkuvatov, Zainidin K. (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
The formulation for the curved crack in a finite plate is established. The technique is the curved crack in a finite plate is divided into two sub-problems i.e. the curved crack problem in an infinite plate and the finite plate without crack. For the first problem, the curved problem is formulated into Fredholm integral equation, where as for the second problem the complex boundary integral equations based on complex variables are considered. The solution of the coupled boundary integral equations gives the solution on the domain of the boundary.